2021
DOI: 10.1002/mbo3.1199
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling analysis of the vitamin B12 producer Propionibacterium freudenreichii

Abstract: Vitamin B 12 (VB 12 ) is an indispensable cofactor of metabolic enzymes and has been widely used in the food and pharmaceutical industries. In this study, the effects of medium composition on VB 12 production by Propionibacterium freudenreichii were evaluated and optimized based on statistical experiments. The results showed that glucose, yeast extract, KH 2 PO 4 , and glyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…These results suggested that the growth and production of our strain were limited not only by the lack of carbon source but also by other factors such as propionic acid inhibition. The latter effect has been widely reported previously [32] and propionic concentration in the final stages of the cultures was probably too high for our strain, around 18 g/L in the batch processes. Considering this inhibition, a fed-batch strategy without a mechanism for propionic acid elimination/ removal (for example, an expanded bed reactor like the one used in [34]) does not seem to be a viable strategy for cobalamin production.…”
Section: Fed-batch With Dmbi Induction At 72 Hsupporting
confidence: 57%
See 2 more Smart Citations
“…These results suggested that the growth and production of our strain were limited not only by the lack of carbon source but also by other factors such as propionic acid inhibition. The latter effect has been widely reported previously [32] and propionic concentration in the final stages of the cultures was probably too high for our strain, around 18 g/L in the batch processes. Considering this inhibition, a fed-batch strategy without a mechanism for propionic acid elimination/ removal (for example, an expanded bed reactor like the one used in [34]) does not seem to be a viable strategy for cobalamin production.…”
Section: Fed-batch With Dmbi Induction At 72 Hsupporting
confidence: 57%
“…Other P. freudenreichii wild-type strains presented similar values compared to our static condition in terms of CNCbl volumetric production. For example, Liu et al reported productions with their non-optimized media of around 3.81 mg/L [32] and Chamlagain and coworkers reported a production of 5.3 mg/L in whey-based media [23].…”
Section: Culture Characterization In Shake-flasks Agitation Effect Du...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prices for the vitamins produced are significantly higher [96,97]. Vitamin extraction from microorganisms involves different processes [96][97][98][99][100][101][102][103][104][105][106][107]:…”
Section: Microbial Production Of Essential Vitaminsmentioning
confidence: 99%
“…However, the prices for the vitamins produced are significantly higher [ 96 , 97 ]. Vitamin extraction from microorganisms involves different processes [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]: Cell disruption: Break open the bacterial cells to release the intracellular contents, including the vitamin. Cell disruption methods can include mechanical disruption (e.g., bead milling, high-pressure homogenization) or enzymatic treatments.…”
Section: Microbial Natural Products Via Fermentation and Their Potent...mentioning
confidence: 99%